Data encryption in public cloud using multi-phase encryption model - Choudhury, Snata; Kirubanand, V.B. (International Journal of Engineering and Technology, 2018)
Cloud computing the most used word in the world of Information Technology, is creating huge differences in IT industry. Nowadays huge amount of data is being generated and the researchers are finding new ways of managing these data. Basically, the word cloud refers to a virtual database that stores huge data from various clients. There are three types of cloud public, private and hybrid. Public cloud is basically for general users where users can use cloud services free or by paying. Private cloud is for any particular organizations and hybrid one is basically combine of both. Cloud offers various kind of services such as IAAS, PAAS, SAAS where services like platform for running any application, accessing the huge storage, can use any application running under cloud are given. The cloud also has a disadvantage regarding the security for the data storage facility. Basically, the public cloud is prone to data modification, data hacking and thus the integrity and confidentiality of the data is being compromised. Here in our work the concern is to protect the data that will be stored in the public cloud by using the multi-phase encryption. The algorithm that we have proposed is a combination of Rail Fence cipher and Play Fair cipher.